Antibacterial Potentiality Testing of Pineapple Core Extract (Ananas comosus (L.) Merr) Against Methicillin-resistant Staphylococcus aureus (MRSA) with Vancomycin Control (Microbiology Indonesia, 2017)
Staphylococcus aureus is one of major pathogens causing serious infection. Penicillin antibiotic is one of therapies against Staphylococcus infection. However, inadequate and irrational use of antibiotic causes resistance and emerges incidence of methicillin-resistant Staphylococcus aureus (MRSA). Herbal medicine from pineapple core extract is hopefully can reduce the incidence of antibiotics resistance. This research was conducted to investigate the antibacterial activity of pineapple core extract against MRSA.This research is true experimental with post-test controlled group design. Pineapple core was extracted by maceration method. Ethanol extract of pineapple core is dissolved with sterilized water and obtained concentration of 750, 500, 250, 187.5, 125, and 62.5 mg/ml. The minimum inhibitory concentration (MIC) and minimum bactericidal concentration (MBC) were determined by broth dilution test with five replications. Vancomycin was used as control group. MIC was observed visually by comparing turbidity of solutions after incubation at 37oC for 24 hours. Then these solutions were cultured on nutrient agar plates at 37oC for 24 hours. MBC was observed visually by inspecting the presence of bacterial colonies growth.The Minimum Inhibitory Concentration (MIC) could not be determined due to no turbidity changes. Vancomycin cannot be used for determining MIC. Cultures on nutrient agar plates had no colonies growth in concentrations of 750 and 500 mg/ml. Thus, the Minimum Bactericidal Concentration (MBC) was 500 mg/ml.Pineapple core extract contains bromelain, flavonoid, saponin, and tanin, which have antibacterial effect. In summary, pineapple core extract has antibacterial effect against methicillin-resistant Staphylococcus aureus (MRSA) with MBC of 500 mg/ml.